THE EFFECT OF LEVERAGE, LIQUIDITY, AND COMPANY AGE ON TRANSFER PRICING WITH AUDIT QUALITY AS A MODERATING VARIABLE AND FINANCE PERFORMANCE AS A MEDIATION VARIABLE - Mohamad Zulman Hakim; Hanifah Nur Azizah; Santiana; Esa Nur Oktafianis; Syahla Lealany (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
This study investigates the effects of leverage, liquidity, and company age on transfer pricing practices, with audit quality as a moderating variable and financial performance as a mediating variable. The research objects are firms in the basic materials industry listed on the Indonesia Stock Exchange (IDX) over the 2021–2024 period. A quantitative approach was adopted, utilizing panel data regression techniques, while sample selection was conducted through purposive sampling based on predefined criteria. The empirical findings reveal that leverage and liquidity exhibit a significant positive effect on transfer pricing, whereas company age demonstrates no statistically significant influence. Audit quality was found to significantly amplify the relationship between leverage and transfer pricing, yet it did not moderate the associations involving liquidity or company age. Furthermore, financial performance significantly mediated the liquidity-transfer pricing nexus but did not serve as a mediator for leverage or company age. These results confirm that both internal financial conditions and external oversight mechanisms, particularly audit quality, play crucial roles in controlling transfer pricing practices within Indonesia’s basic materials sector. The implications underscore the importance of strengthening audit functions and monitoring financial indicators to curb aggressive transfer pricing strategies, thereby informing regulatory and corporate governance policy enhancements.